Analysis of the current situation of female induced abortion under China’s “three-child policy” - Lingna Huang; Jinwen Zhang; Kuncan Chen; Kairui Lin; Xin Wu; Yushan Hong; Yihua Ni; Xiujuan Chen (PLoS ONE, 2026)
Objective To assess the changes in the characteristics of women undergoing induced abortion and their contraceptive choices before and after the implementation of the “three-child” policy, and to inform strategies for improving reproductive health services in China. Methods We conducted a retrospective comparative study at a tertiary maternity hospital in Fujian, China. Women who underwent induced abortion between 31 May 2019 and 30 May 2020 (pre-policy period) and those who underwent the procedure between 31 May 2023 and 30 May 2024 (post-policy period) were included. We used R software (version 4.3.2) to compare contraceptive use and method choices prior to the abortion, as well as the primary reasons for unintended pregnancy between pre- and post-policy periods. Results In the pre-policy period, non-use of contraception was the leading cause of unintended pregnancy (43.38%), primarily attributed to a perception of low pregnancy risk. Among contraceptive users, condoms were the most common method (26.47%). Post-policy, the rate of contraceptive non-use decreased to 32.19%. However, reliance on low-efficacy methods persisted, with condoms (43.49%) and withdrawal (23.51%) remaining predominant. Conclusion Non-use of contraception and reliance on low-efficacy methods remained the primary contributors to unintended pregnancies among women undergoing induced abortion both before and after the three-child policy. Higher educational attainment was associated with lower contraceptive failure risk. These findings underscore the urgent need to improve access to effective contraceptive methods and strengthen reproductive health education to reduce unintended pregnancies and safeguard women’s reproductive health.